946 Transforming the Morbidity and Mortality Review Process: Customised Digitalisation Helps Us Learn from Mistakes. (19th August 2022) - James, Eleanor; O'Shea, Kathryn; Kwok, Chun; Partridge, Roland; Taylor, Josef; Almond, Sarah
Abstract: Aim: Morbidity and Mortality (M&M) review is an important component of clinical governance in surgical practice. Constructive discussions are crucial for improving patient outcomes and quality of care. We aimed to transform the M&M review process within the paediatric surgical department of our tertiary referral centre. Method: A critical assessment of our previous system identified weaknesses which we addressed by sequential changes in software and meeting organisation. Clinical staff developed a customised web-based reporting platform, followed by a more sophisticated mobile application for smart phones/tablets, allowing users to explore all reported cases and discussions, and to monitor actions from previous cases. The introduction of triage meetings structured the agenda and content for M&M meetings and monitoring of agreed recommendations/proposed actions ensured service improvement. Results: The introduction of the reporting platform increased case reporting (11 vs 21 cases/month). The subsequent development of our mobile application standardised the recording of case discussion with contributing factors recorded for 100% of cases discussed. Recommendations are logged and tracked within the app's dashboard which shows every report coded by key words so case series can be identified, and audits easily facilitated. Conclusions: M&M meetings are crucial in improving patient safety and quality of care and are pivotal to surgical training. Our mobile application simplifies, and encourages, case reporting and provides a platform to facilitate structured M&M conferences. This project demonstrates innovative uses of technology can facilitate quality improvement from M&M meetings, support audits and enhance education of surgical trainees.